HEALTHCARE PERFORMANCE MEASUREMENT: IDENTIFICATION OF METRICS FOR THE LEARNING AND GROWTH BALANCED SCORECARD PERSPECTIVE - Emami, Samin; Doolen, Toni (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
<span style="mso-ascii-font-family: 'Times New Roman'; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: major-bidi; mso-bidi-language: FA;" lang="EN-US">While there is substantial literature devoted to measuring the performance of hospitals and clinics in terms of indicators such as health outcomes and finances, it is vital for hospitals and clinics to also develop a set of forward-looking metrics at the operational level that drive all aspects of performance. The purpose of this research is to identify and prioritize a set of metrics within one perspective of the Balanced Scorecard framework, called learning and growth, which aims at sustaining innovation, change, and continuous improvement. Using Analytic Hierarchy Process, the data provided by medical managers was analyzed to determine the most important learning and growth categories and metrics within each category. The results showed that “human capital” metrics have the most significant impact on the performance of the participating hospitals/clinics. The results also provide practitioners with metrics spanning each of the four performance categories identified to the learning and growth perspective.